Acupuncture for Irritable Bowel Syndrome: 2-Year Follow-Up of a Randomised Controlled Trial. Issue 1 (February 2017) - MacPherson, Hugh; Tilbrook, Helen; Agbedjro, Deborah; Buckley, Hannah; Hewitt, Catherine; Frost, Chris
Background: A recent randomised controlled trial (RCT) of acupuncture as a treatment for irritable bowel syndrome (IBS) demonstrated sustained benefits over a period of 12 months post-randomisation. Aim: To extend the trial follow-up to evaluate the effects of acupuncture at 24 months post-randomisation. Methods: Patients in primary care with ongoing IBS were recruited to a two-arm pragmatic RCT of acupuncture for IBS. Participants were randomised to the offer of up to 10 weekly sessions of acupuncture plus usual care (n=116 patients) or to continue with usual care alone (n=117). The primary outcome was the self-reported IBS symptom severity score (IBS SSS) measured at 24 months post-randomisation. Analysis was by intention-to-treat using an unstructured multivariate linear model incorporating all repeated measures. Results: The overall response rate was 61%. The adjusted difference in mean IBS SSS at 24 months was −18.28 (95% CI −40.95 to 4.40) in favour of the acupuncture arm. Differences at earlier time points estimated from the multivariate model were: −27.27 (−47.69 to −6.86) at 3 months; −23.69 (−45.17 to −2.21) at 6 months; −24.09 (−45.59 to −2.59) at 9 months; and −23.06 (−44.52 to −1.59) at 12 months. Conclusions: There were no statistically significant differences between the acupuncture and usual care groups in IBS SSS at 24 months post-randomisation, and the point estimate for the mean difference was approximately 80% of the size of the statistically significant results seen at 6, 9 and 12 months. Trial registration number: ISRCTN08827905.